Cryptographically secure random number generator with chaotic additional input - Ozkaynak, Fatih (Springer, 2014)
Random number generators are an important tool for cryptographic applications. In cryptographic protocol, randomness is essential properties since inadequate source of randomness can be effect security of whole system. This paper describes requirements of a robust random generator and proposes hybrid architecture to realize these requirements. Security analysis shows that output of proposed generator looks random. Therefore, proposed generator is used for cryptographic solutions.
Keywords: Random number generator; Hybrid generator; Additional input; Chaos